Prispevek k poznavanju favne hroščev v Jami pri Lipniški skali - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2016)
Results of a nine years sampling of the beetle fauna in the cave Jama pri Lipniški skali (north-western part of Slovenia) are presented. Sixteen species in all were found.
Keywords: beetles; Bothrideridae; Carabidae; Cholevidae; Coleoptera; Cryptophagidae; hrošči; Leiodidae; new records; Slovenia; Slovenija; Staphylinidae; Trechinae